Lung Ultrasound-Guided Non-Fiberobronchoscopic Bronchoalveolar Lavage for Neonatal Atelectatic Pulmonary Disease Treatment: Clinical Practice Guidelines Based on International Expert Consensus - Jing Liu; Ya-Li Guo; Peng Jiang; Xian Zhang; Bi-Ying Deng; Zun-Jie Liu; Xiao-Xiao Wang; Yuan Hong; Xiao-Ling Ren; Meng-Ru Zhao; Ning Li; Cai-Xuan Xie; et al. (Diagnostics, 2026)
Severe pulmonary diseases, including atelectasis, pneumonia, and meconium aspiration syndrome, are major causes of neonatal respiratory distress, weaning difficulties, ventilator or oxygen dependence, prolonged oxygen requirements, extended hospitalization, and poor prognosis. The lack of simple and effective treatment strategies seriously endangers the survival and health of newborns, particularly premature infants. Recent advances in lung ultrasound (LUS) technology have made LUS-guided non-fiberobronchoscopic bronchoalveolar lavage (NFB-BAL) a promising solution. This approach addresses the limitations of conventional BAL in neonates by enabling accurate diagnosis, precise lesion localization, and dynamic procedural monitoring, hence reducing complications. Based on international expert consensus, these guidelines were developed to improve knowledge and promote the application of this technology and enhance operational standardization to ensure its effectiveness and safety. These guidelines contain 17 recommendations on 13 key clinical issues for reference and implementation in clinical practice. The wide application of these guidelines is expected to help significantly improve the prognosis of critically ill newborns with atelectatic pulmonary diseases.